RANCANG BANGUN PRODUK SUBSTITUSI SISTEM DATA LOGGER ALIRAN DAN TEKANAN AIR PADA ALIRAN PIPA TERTUTUP MENGGUNAKAN KOMUNIKASI LoRaWAN - Supriyanto, Hadi; Aji, Wisnu; Martawireja, Abdur Rohman Harits; Abadi, Sarosa Castrena; Mulia, Sandy Bhawana; Candra, Wahyu Adhi; Pratama, Rizki Aji; Adi, Reka; Naufaldo, Naufaldo (P3M Politeknik Negeri Indramayu, 2024)
The availability of data loggers as data acquisition is still limited to sensor levels and the data loggers have not been produced in Indonesia. This makes it difficult for monitors to obtain data such as water pressure and water discharge data. The solution to this problem is to reduce the import cost of purchasing data loggers from abroad by developing data loggers that are able to take data on water level, water pressure. This study aims to determine how the design and performance of data logger system substitution products flow and water pressure using LoRa WAN communication. The test results show that the Water Flow and Pressure Data logger System functions according to the design that has been made with error readings from the itron cyble sensor of ?? and a pressure sensor reading error of 20.66%. The Packet Loss value of sending data from the data logger device is directly proportional to the distance where the smallest packet loss value is 13% at a distance of 50m and 80% at a distance of 2800m.